2012
DOI: 10.1111/tpj.12034
|View full text |Cite
|
Sign up to set email alerts
|

RNA polymerase V targets transcriptional silencing components to promoters of protein‐coding genes

Abstract: SUMMARY Transcriptional gene silencing controls transposons and other repetitive elements through RNA-directed DNA methylation (RdDM) and heterochromatin formation. A key component of the Arabidopsis RdDM pathway is ARGONAUTE4 (AGO4), which associates with siRNAs to mediate DNA methylation. Here, we show that AGO4 preferentially targets transposable elements embedded within promoters of protein-coding genes. This pattern of AGO4 binding cannot be simply explained by the sequences of AGO4-bound siRNAs; instead,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
89
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(93 citation statements)
references
References 45 publications
3
89
0
1
Order By: Relevance
“…This suggests that RdDM may not be a crucial requirement for silencing all transposons (5,6,30). Instead, this activity may be critical for maintaining the silencing of the transposons that are located near genes (31). Indeed, the analysis of changes in DNA methylation in the mop1 and mop3 mutants that perturb components of the maize RdDM system revealed that the loss of mCHH at the transposon edges near genes can often result in additional loss of CG/CHG methylation in the transposon.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that RdDM may not be a crucial requirement for silencing all transposons (5,6,30). Instead, this activity may be critical for maintaining the silencing of the transposons that are located near genes (31). Indeed, the analysis of changes in DNA methylation in the mop1 and mop3 mutants that perturb components of the maize RdDM system revealed that the loss of mCHH at the transposon edges near genes can often result in additional loss of CG/CHG methylation in the transposon.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies from Arabidopsis further suggest that RdDM is enriched in specific genomic contexts such as recently inserted transposons and promoters (Zheng et al, 2012;Zhong et al, 2012). In maize, both 24-nucleotide siRNAs and CHH methylation are more abundant near genes than in the expanses of repetitive intergenic DNA, giving rise to the term CHH islands (Gent et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…RdDM is primarily associated with the repression of transposons, but it can indirectly affect gene expression through genomic imprinting (Vu et al, 2013) and paramutation (reviewed in Hollick, 2012). Multiple studies have suggested that RdDM is not a uniform feature of heterochromatin in plant genomes but is enriched in particular heterochromatic regions, including 5S ribosomal loci, long terminal repeats of retrotransposons, DNA transposons, and repetitive elements in general when close to genes (Onodera et al, 2005;Zheng et al, 2012;Zhong et al, 2012;Gent et al, 2013;Regulski et al, 2013;Stroud et al, 2013;Sun et al, 2013;Zemach et al, 2013;Diez et al, 2014;Wei et al, 2014). In Arabidopsis, methylation in long transposons near centromeres can be mediated by the DNA methyltransferase CMT2 without the involvement of RdDM (Zemach et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The use of null mutants to control for nonspecific antibody binding in ChiP-seq studies in Arabidopsis seedlings demonstrated that many peaks are false-positives (Wierzbicki et al, 2012;Zheng et al, 2012). Efficient siRNA would be required for this approach to be adopted in mammalian cell culture.…”
Section: General Features Of Genome-wide Tcf Bindingmentioning
confidence: 99%